Intravenous Immunoglobulin and Mycophenolate Mofetil for Long-Standing Sensory Neuronopathy in Sjögren's Syndrome - Maria Giovanna Danieli; Lucia Pettinari; Ramona Morariu; Fernando Monteforte; Francesco Logullo (Case Reports in Immunology)
Sensory neuronopathy is described in association with the Sjögren's syndrome (SS). We studied a 55-year-old woman with a 4-year history of progressive asymmetric numbness, distal tingling, and burning sensation in upper and lower limbs. In a few months, she developed ataxia with increased hypoanaesthesia. Electrodiagnostic tests revealed undetectable distal and proximal sensory nerve action potential in upper and lower limbs. Cervical spine magnetic resonance showed a signal hyperintensity of posterior columns. Previous treatment with high-dose glucocorticoids and azathioprine was ineffective. A combined treatment with intravenous immunoglobulin and mycophenolate mofetil was followed by a progressive and persistent improvement. This case documented the efficacy and the safety of the coadministration of intravenous immunoglobulin and mycophenolate mofetil in sensory neuronopathy associated with SS refractory to conventional immunosuppressive therapy.